Transcriptomic Analysis Implies That GA Regulates Sex Expression via Ethylene-Dependent and Ethylene-Independent Pathways in Cucumber (Cucumis sativus L.) - Zhang, Yan; Zhao, Guiye; Li, Yushun; Mo, Ning; Zhang, Jie; Liang, Yan (Frontiers in Plant Science, 2017)
Sex differentiation of flower buds is an important developmental process that directly affects fruit yield of cucumber (Cucumis sativus L.). Plant hormones such as gibberellins (GAs) and ethylene can promote development of male and female flowers, respectively, however, the regulatory mechanisms of GA-induced male flower formation and potential involvement of ethylene in this process still remain unknown. In this study, to unravel the genes and gene networks involved in GA-regulated cucumber sexual development, we performed high throughout RNA-Seq analyses that compared the transcriptomes of shoot tips between GA3 treated and untreated gynoecious cucumber plants. Results showed that GA3 application markedly induced male flowers but decreased ethylene production in shoot tips. Furthermore, the transcript levels of M (CsACS2) gene, ethylene receptor CsETR1 and some ethylene-responsive transcription factors were dramatically changed after GA3 treatment, suggesting a potential involvement of ethylene in GA-regulated sex expression of cucumber. Interestingly, GA3 down-regulated transcript of a C-class floral homeotic gene, CAG2, indicating that GA may also influence cucumber sex determination through an ethylene-independent process. These results suggest a novel model for hormone-mediated sex differentiation and provide a theoretical basis for further dissection of the regulatory mechanism of male flower formation in cucumber.